Protective effect of anthrax toxin receptor 2 polymorphism rs4333130 against the risk of ankylosing spondylitis. Issue 28 (10th July 2020) - Xu, Haitao; Qu, Yiming
Abstract: Background: The present study was performed to statistically explore the effect of anthrax toxin receptor 2 (ANTXR2) polymorphism rs4333130 on individual susceptibility to ankylosing spondylitis (AS) using the method of meta-analysis. Methods: All of the eligible reports were retrieved from well-known electronic databases. The strength of the association between ANTXR2 polymorphism rs4333130 and the susceptibility to AS was evaluated using pooled odds ratios (ORs) with 95% confidence intervals (95% CIs). In addition, subgroup analysis was also performed on the basis of ethnicity to further explore specific correlation between our studied polymorphism and the disease risk. Inter-study heterogeneity was detected with Q test, and P  < .05 was considered statistically significant. Sensitivity analysis was implemented through removing each of eligible studies and then recalculating overall effects to test the reliability of final estimates. Publication bias among included studies was inspected with both Begg funnel plot and Egger regression test. Results: A total of 6 eligible papers were finally incorporated into the present meta-analysis. In total analysis, ANTXR2 polymorphism rs4333130 was significantly related to decreased risk of AS under CC versus TT, CC + TC versus TT, CC versus TT + TC, C versus T and TC versus TT contrasts (OR = 0.35, 95% CI = 0.20–0.64; OR = 0.81, 95% CI = 0.69–0.95; OR = 0.38, 95% CI = 0.21–0.68; OR = 0.89, 95% CI = 0.84–0.95; OR = 0.84, 95% CI = 0.72–0.99). Moreover, a similar effect was also observed in Asian and Caucasian subgroups under corresponding genetic models after stratification analysis based on ethnicity. Conclusion: ANTXR2 polymorphism rs4333130 may function as a protective factor against AS incidence.